Autophagy inhibition suppresses Newcastle disease virus-induced cell death by inhibiting viral replication in human breast cancer cells - Rozilah, Megat Irfan; Yusoff, Khatijah; Chia, Suet Lin; Ismail, Saila (Academic Press Inc., 2024)
Newcastle disease virus (NDV) is an oncolytic virus which selectively replicates in cancer cells without harming normal cells. Autophagy is a cellular mechanism that breaks down unused cytoplasmic constituents into nutrients. In previous studies, autophagy enhanced NDV-induced oncolysis in lung cancer and glioma cells. However, the effect of autophagy inhibition on NDV-induced oncolysis in breast cancer cells remains unknown. This study aimed to examine the effect of autophagy inhibition on NDV-induced oncolysis in human breast cancer cells, MCF7. To inhibit autophagy, we knocked down the expression of the autophagy protein beclin-1 (BECN1) by short interfering RNA (siRNA). The cells were infected with the recombinant NDV strain AF2240 expressing green fluorescent protein. We found that NDV induced autophagy and knockdown of BECN1 significantly reduced the NDV-induced autophagy in MCF7 cells. Importantly, BECN1 knockdown significantly suppressed cell death by inhibiting viral replication, as observed at 24 h post infection. Overall, our data suggest that autophagy inhibition may not be a suitable strategy to enhance NDV oncolytic efficacy against breast cancer.